Diagnosis And Comprehensive Management Of Thyroid Storm: A Literature Review - Dewi Puspitorini Husodo; Gede Naradhea Pramudiantara; Galang Edi Wibawa; Ni Wayan Puspa Wijaya Suryantarini; Najwa Widad; Rofi Bramantyo (Jurnal Ilmu Kedokteran dan Kesehatan, 2026)
Thyroid storm is a life-threatening endocrine emergency characterized by severe hypermetabolism and multiorgan dysfunction with mortality rates ranging from 10–30%. Delayed diagnosis and inappropriate management significantly contribute to poor clinical outcomes. This study is a literature review conducted through systematic searches in PubMed, Google Scholar, Wiley, Springer, and ScienceDirect databases for articles published between 2015 and 2025 using keywords “thyroid storm,” “hyperthyroidism,” “emergency,” “diagnosis,” and “management.” A total of 30 relevant articles, including case reports, cohort studies, and original research, were analyzed descriptively. The findings show that thyroid storm occurs in approximately 1–2% of hospitalized hyperthyroid patients, with global mortality reaching 20–30% and 8–25% in Indonesia. Early diagnosis using the Burch-Wartofsky Point Scale (score 45), combined with Japanese Thyroid Association criteria, improves diagnostic accuracy and facilitates prompt treatment. Initial management focuses on ABCDE stabilization, fluid resuscitation, and supportive care, followed by pharmacological therapy including antithyroid drugs (propylthiouracil or methimazole), iodine, beta-blockers, and corticosteroids. In refractory cases, plasmapheresis may be required, while definitive therapy such as thyroidectomy or radioiodine is performed after achieving euthyroid status. Thyroid storm requires rapid recognition and a structured, multidisciplinary management approach, and integration of validated diagnostic tools with comprehensive treatment strategies is essential to improve patient outcomes and reduce mortality.